That lady in ermine = Die Frau im Hermelin - Raphaelson, Samson 1894-1983 (Twentieth Century Fox Home Entertainment, 2012)
"When a dashing Colonel invades her castle and takes her hostage, will the Countess take her revenge ... or fall in love?"--Container
Spielfilm, Orig.: USA, 1948
Keywords: Musikfilm; Filmkomödie; Aristocracy (Social class) / Italy / Drama; Hungarians / Italy / Drama; Bergamo (Italy) / History / Drama; Italy / History / War of 1860-1861 / Drama; Aristocracy (Social class); Hungarians; Italy; Italy / Bergamo; 1860-1861; DVD-Video discs; Drama; Feature films; Fiction films; History; Musical films; Comedy films; Films musicaux; Films comiques; Films de fiction; Film; DVD-Video